Homogenisation of milk and its effect on sensory and physico-chemical properties of yoghurt (2014)
This study was designed to evaluate the chemical composition, sensory properties and microbial load of differently homogenized milk for yoghurt-making. Milk was homogenized with a hand whisker (HW), pressure sprayer (PS) and high-speed mixer (HM) while the control was not homogenized (NH) prior to yoghurt-making. Samples were stored in a refrigerator for 10 days at 4°C and thereafter examined for microbial counts using pour plate technique. Results show that homogenization had no significant (p > 0.05) influence on taste and flavor of yoghurt. The chemical composition of the yoghurt samples in all the treatment groups were improved as the days in storage progressed. The highest total viable count (TVC), coliform and fungal counts were obtained with NH while PS recorded the least counts.